Effects of combined ciprofloxacin and Neulasta therapy on intestinal pathology and gut microbiota after high-dose irradiation in mice - Timothy S. Horseman; Timothy S. Horseman; Andrew M. Frank; Georgetta Cannon; Min Zhai; Matthew G. Olson; Bin Lin; Xianghong Li; Lisa Hull; Mang Xiao; Juliann G. Kiang; Juliann G. Kiang; et al. (Frontiers Media S.A., 2024)
IntroductionTreatments that currently exist in the strategic national stockpile for acute radiation syndrome (ARS) focus on the hematopoietic subsyndrome, with no treatments on gastrointestinal (GI)-ARS. While the gut microbiota helps maintain host homeostasis by mediating GI epithelial and mucosal integrity, radiation exposure can alter gut commensal microbiota which may leave the host susceptible to opportunistic pathogens and serious sequelae such as sepsis. To mitigate the effects of hematopoietic ARS irradiation, currently approved treatments exist in the form of colony stimulating factors and antibiotics: however, there are few studies examining how these therapeutics affect GI-ARS and the gut microbiota. The aim of our study was to examine the longitudinal effects of Neulasta and/or ciprofloxacin treatment on the gut microbiota after exposure to 9.5 Gy 60Co gamma-radiation in mice.MethodsThe gut microbiota of vehicle and drug-treated mice exposed to sham or gamma-radiation was characterized by shotgun sequencing with alpha diversity, beta diversity, and taxonomy analyzed on days 2, 4, 9, and 15 post-irradiation.ResultsNo significant alpha diversity differences were observed following radiation, while beta diversity shifts and taxonomic profiles revealed significant alterations in Akkermansia, Bacteroides, and Lactobacillus. Ciprofloxacin generally led to lower Shannon diversity and Bacteroides prevalence with increases in Akkermansia and Lactobacillus compared to vehicle treated and irradiated mice. While Neulasta increased Shannon diversity and by day 9 had more similar taxonomic profiles to sham than ciprofloxacin-or vehicle-treated irradiated animals. Combined therapy of Neulasta and ciprofloxacin induced a decrease in Shannon diversity and resulted in unique taxonomic profiles early post-irradiation, returning closer to vehicle-treated levels over time, but persistent increases in Akkermansia and Bacteroides compared to Neulasta alone.DiscussionThis study provides a framework for the identification of microbial elements that may influence radiosensitivity, biodosimetry and the efficacy of potential therapeutics. Moreover, increased survival from H-ARS using these therapeutics may affect the symptoms and appearance of what may have been subclinical GI-ARS.